Effect of Biosynthesis ZnO-NPs on Renal Injury Caused by Hydrogen Peroxide in Adults Male Rats - AL-Kurdy, Masar J.; Kazaal , Meraim A. (Iraqi Journal of Science, 2025)
Nanoparticles produced through biological synthesis have shown significant potential in various therapeutic applications. This study was designed to explore the potential of biosynthesized zinc oxide nanoparticles (ZnO-NPs) in alleviating kidney disorders, which are among the most prevalent health issues globally. The study included the preparation of ZnO-NPs using black currant extract. The ZnONPs were formed by dissolving black currant in a zinc oxide solution with pH adjusted to 12. During the mixing process, Zinc acetate dehydrate was reduced to ZnONPs, resulting in a color change of the solution from white to pale yellow color within a few minutes. The synthesized ZnONPs were separated by centrifugation (4000rpm/ 5min), characterized by x-ray diffraction (XRD), Scanning Electron Microscopy (SEM) Fourier Transmission Infrared Spectroscopy (FT-IR) methods. The effectiveness of these particles was tested on adult male rats whose kidney disorders were induced by H₂O₂. The adult male rats were divided into four groups based on their dosage: the first (G1) received 0.5% H2O2, the second (G2) received 0.5% H2O2 and ZnO-NPs (10 µg /kg), and the third group received ZnO-NPs (10 µg /kg). They were mixed along with the control group, which only got distilled water. The findings indicated that G1 had the highest levels of bilirubin, creatinine, and urea nitrogen at rates of 66.15, 44.46, and 4.60 µmol/l, respectively. In contrast, G2 showed levels of 45.52, 36.79, and 2.27 µmol/l, respectively, and G3 had rates of 41.41, 34.38, and 1.33 µmol/l, respectively. A high concentration of Malondialdehyde (MDA) was detected in group G1 (14.30 µmol/l), a lower concentration in group G2 (9.91 µmol/l), and the lowest concentration of MDA in group G3 (6.59 µmol/l), which was close to the control group (6.55 µmol/l). As well as found significant changes in MDA concentrations between groups G1 and G3 or control. Glutathione peroxidase (GPX) levels dropped in group G1 (2.26 µmol/l) but rose in groups G3 (4.72 µmol/l) and control (4.68 µmol/l). Histologically, the animals treated with both control and ZnO-NPs had similar approximate kidney structures, characterized by regular renal tubules and glomeruli. However, sections of the kidneys of H2O2-treated rats were inspected under a microscope, and necrotized glomeruli, atrophic glomeruli, and renal tubular epithelial necrosis were seen. The cortex of the ZnO-NPs treated group G2 was normal, but the glomeruli and some tubules had been largely damaged. Our results suggest that ZnO-NPs play a beneficial role in mitigating the harmful effects of H₂O₂-induced kidney damage in rats. Where ZnO-NPs can be considered as an antioxidant, and protective agent against kidney injury and cytoprotective activity.